π-Hole Tetrel Bonds—Lewis Acid Properties of Metallylenes - Sławomir J. Grabowski (Crystals, 2022)
The MP2/aug-cc-pVTZ calculations were performed on the dihalometallylenes to indicate their Lewis acid and Lewis base sites. The results of the Cambridge Structural Database search show corresponding and related crystal structures where the tetrel center often possesses the configuration of a trigonal bipyramid or octahedron. The calculations were also carried out on dimers of dichlorogermylene and dibromogermylene and on complexes of these germylenes with one and two 1,4-dioxide molecules. The Ge⋯Cl, Ge⋯Br, and Ge⋯O interactions are analyzed. The Ge⋯O interactions in the above mentioned germylene complexes may be classified as the π-hole tetrel bonds. The MP2 calculations are supported by the results of the Quantum Theory of Atoms in Molecules (QTAIM) and the Natural Bond Orbital (NBO) approaches.